(untitled) (Islamic Studies Journal for Social Transformation, 2024)
Science education in Madrasah Ibtidaiyah (MI) plays an important role in shaping the character and competencies of the 21st century based on Islamic values. However, science learning in MI is still dominated by conventional methods that have not integrated spiritual and technological valueoptimally. This study aims to analyze the integration of the Technological Pedagogical Content Knowledge (TPACK) approach with the values of the Rahmatan Lil Alamin Student Profile (PPRA) in science learning in Madrasah Ibtidaiyah. The aspects analyzed include the use of the TPACK approach in science learning, instilling PPRA values, the urgency of instilling PPRA values in MI, strategies for instilling PPRA values in MI, integration between the TPACK model and instilling PPRA values in science learning in MI, and the synergy between the two. This study uses a literature study method by reviewing relevant scientific sources and policy documents. The results of the study indicate that the TPACK model that combines content knowledge, pedagogy, and technology is able to create interactive and meaningful science learning. Meanwhile, PPRA values such as faith, noble morals, religious moderation, love for the environment, and social responsibility provide a character dimension that enriches the learning process. The synergy between TPACK and PPRA is believed to be able to create a holistic learning experience that not only enriches students’ intellectual intelligence, but also strengthens their spirituality and social awareness. This study recommends the development of a science learning strategy in MI that is technology-based, contextual, and has Islamic values as an effort to realize transformative madrasah education and rahmatan lil alamin.